SPE Annual Technical Conference and Exhibition 2018
DOI: 10.2118/191574-ms
|View full text |Cite
|
Sign up to set email alerts
|

Delivering Drilling Automation II – Novel Automation Platform and Wired Drill Pipe Deployed on Arctic Drilling Operations

Abstract: This paper presents a case history of drilling automation system pilot deployment, inclusive of wired drill pipe on an Arctic drilling operation. This builds on the body of work that BP (the operator) previously presented in 2017 related to the deployment of an alternate drilling automation system. The focus will be on the challenges and lessons learned during this deployment over a series of development wells. Two major aspects of technology were introduced during this pilot, the first being a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 8 publications
0
1
0
1
Order By: Relevance
“…A construção de um poço inclui várias etapas de segurança e notadamente, de limpeza, pois ao realizar o procedimento de perfuração, o fluido retirado vem contaminado por uma série de elementos. Assim, entra em função o sistema de circulação de fluidos da sonda, que é responsável pelo bombeamento dos fluidos de perfuração e da pasta de cimento para o poço; cuja função será carregar o cascalho para fora do poço, conferir pressão hidrostática ao poço, lubrificar e refrigerar a broca, bem como depositar uma camada de reboco na parede do poço (ISRAEL et. al., 2018).…”
Section: Resultados E Discussõesunclassified
“…A construção de um poço inclui várias etapas de segurança e notadamente, de limpeza, pois ao realizar o procedimento de perfuração, o fluido retirado vem contaminado por uma série de elementos. Assim, entra em função o sistema de circulação de fluidos da sonda, que é responsável pelo bombeamento dos fluidos de perfuração e da pasta de cimento para o poço; cuja função será carregar o cascalho para fora do poço, conferir pressão hidrostática ao poço, lubrificar e refrigerar a broca, bem como depositar uma camada de reboco na parede do poço (ISRAEL et. al., 2018).…”
Section: Resultados E Discussõesunclassified
“…The application of standardized procedures under the protection of SOE and FDM functions have shown that automated drilling operations were both possible [5] and increased the efficiency [6]. Attempts have been made to integrate downhole measurements from high-speed telemetry in a closed loop control architecture [7,8]. Also, the control of drilling parameters has been automated using closed loop control [9,10].…”
Section: Introductionmentioning
confidence: 99%